Anatomical Variations of the Nasal Conchae and Nasal Septum and their Relationships with Alterations in the Maxillary Sinus Mucosa: A Study on Cone-beam Computed Tomography Images - Almeida, Luara da Silveira Roberto; Ruffo, Aline da Silva; Devito, Karina Lopes (International Archives of Otorhinolaryngology, 2025)
Introduction In the literature, there is divergence about the relationship between anatomical variations of the turbinates and nasal septum (NS) and alterations in the maxillary sinus (MS) mucosa.Objective To determine, through cone-beam computed tomography (CBCT) images of Brazilian individuals, the prevalence and relationship of anatomical variations of the turbinates and NS with alterations in the mucosa of the MS, as well as to analyze the relationships of these variables with demographic data.Methods The present cross-sectional study involved the analysis of 120 CBCT scans using the i-CAT Vision software, conducted by 2 calibrated examiners. The MS, lower and medium turbinates, and NS were evaluated. Data on gender, age, and the side affected by anatomical variation were also collected. The intra- and interexaminer agreements were assessed using Kappa indices. The association was analyzed using the Chi-squared or Fisher exact tests, and measured by the Phi, Cramer V, or Kendall Tau-C values.Results Most patients presented partial opacification of the MS (89.2%), inferior turbinate hypertrophy (TH) (60.8%), and NS deviation (85%). There were no cases of inferior concha bullosa (CB), while the prevalence of middle CB was of 20%. Variation in the turbinates, CB, and NS were not significantly related to changes in the MS mucosa.Conclusion We can conclude that, in the evaluated sample, there was no significant associations involving the studied variables.
Keywords: maxillary sinus; sinusitis; turbinates; nasal septum; cone-beam computed tomography